Highly oxidized States of Phthalocyaninato Terbium(III) Multiple-Decker Complexes Showing Structural Deformations, Biradical Properties and Decreases in Magnetic Anisotropy - Horii, Yoji; Damjanović, Marko; Ajayakumar, M. R.; Katoh, Keiichi; Kitagawa, Yasutaka; Chibotaru, Liviu; Ungur, Liviu; Mas-Torrent, Marta; Wernsdorfer, Wolfgang; Breedlove, Brian K.; Enders, Markus; Veciana, Jaume; et al. (Chemistry - a European journal, 2020)
Presented here is a comprehensive study of highly oxidized multiple-decker complexes composed of TbIII and CdII ions and two to five phthalocyaninato ligands, which are stabilized by electron-donating n-butoxy groups. From X-ray structural analyses, all the complexes become axially compressed upon ligand oxidation, resulting in bowl-shaped distortions of the ligands. In addition, unusual coexistence of square antiprism and square prism geometries around metal ions was observed in +4e charged species. From paramagnetic 1H NMR studies on the resulting series of triple, quadruple and quintuple-decker complexes, ligand oxidation leads to a decrease in the magnetic anisotropy, as predicted from theoretical calculations. Unusual paramagnetic shifts were observed in the spectra of the +2e charged quadruple and quintuple-decker complexes, indicating that those two species are actually unexpected triplet biradicals. Magnetic measurements revealed that the series of complexes show single-molecule magnet properties, which are controlled by the multi-step redox induced structural changes.
First published: 19 May 2020
Gesehen am 05.11.2021